Análisis sobre los imaginarios del trabajo en los trabajadores informales en la plazoleta la victoria de la ciudad de Quito. - Álvarez Iza, Myriam Alicia (2014)
The present paper summarizes the results of the study on the imaginary work of informal workers in the Square "LA VICTORIA" in the Metropolitan District of Quito, which places look Communication and analysis from the City, in order to identify the conceptions with subjects around work, status, employment relationship, the interaction, the conception of time, space, salary, health. The aspects mentioned to identify each individual develops imaginary that often are not perceived but are present in the daily life of every human being because they are constructed according to their social context.